Ukrainians and Lemkos displaced from the Vistula Operation and Their Descendants in Cemeteries in North-Western Poland - Mieczkowski, Janusz (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
In 1947, the Ukrainian and Lemko minorities were forcibly resettled in Poland and dispersed from south-eastern Poland to the north-west of the country. The displaced persons were subject to various exclusionary restrictions, which even concerned funeral practices/funeral rituals. Cemeteries are treated in the article as a specific place of ethnic and cultural manifestation of groups living in a given area. National identity is understood by the author as a certain lifestyle observed from the outside, creating a “cultural pattern” referring to a specific set of values. The way the dead are remembered is a kind of confirmation of the possibility of maintaining one’s own identity and the prevailing intergroup relations – ethnic and social. The author looks for answers to questions about what possibilities existed to commemorate the deceased after the Vistula operation, identifying them as Ukrainian or Lemko, what favored them and what constituted a barrier.